Lietuvos šiuolaikinės bibliofilijos tyrimų galimybės - Žemaitytė, Kristina (Knygotyra, 2003)
The main objective of this article is to carry out the research of contemporary bibliophily in Lithuania, to reflect on the methods used in the research and to present the results of the research of Lithuanian bibliophiles' libraries which took place in 2002–2003 by the initiative of the Institute of Documentation and Book Science of Vilnius University with the help of questionnaires.In order to understand the condition of bibliophily in Lithuania today it is necessary not only to get acquainted with the work of bibliophiles' clubs but also to analyze personal collections of the members of such clubs and other bibliophiles. The Institute of Documentation and Book Science aspires to research and encourage the expression of bibliophily in contemporary Lithuanian culture.Close co-operation between book scientists and bibliophiles' clubs makes it possible to realize various ideas and research projects. One of such projects is the research of personal libraries of the members of Lithuanian bibliophiles' clubs with the help of the method of questionnaires; collected data was issued in the publication "Bibliophiles about Personal Libraries" in 2001.In 2002, with the purpose to enlarge the data basis on the contemporary bibliophiles' personal libraries, which was necessary for the scientific evaluation of these collections of printings, the questionnaire was expanded and in January 2003 distributed among bibliophiles.The following conclusion can be made after reviewing the results of the research: there is theoretical and practical postulates to distinguish two concepts: a bibliophile and a book lover.